The Efficacy of Tribulus terrestris and Cumminum cyminium Against Sexual Dysfunction in Diabetic Male Rats - Kumar, Ashok; Neupane, Netra P.; Khalilullah, Habibullah; Dahiya, Vinesh; Agrawal, SS; Verma, Amita (Current Traditional Medicine, 2023)
Aim: The aim of the study was to assess the efficacy of Tribulus terristeris and Cumminum cyminium in a standardized diabetic animal model for various pathological conditions of male sexual dysfunction (i.e., loss of libido, erectile dysfunction, and infertility) and compare these herbs with standard drugs. Background: The prevalence of sexual dysfunction is about 40-45% in adult women, and 20-30% of adult men have sexual dysfunction. Sexual dysfunction is more common in men with diabetes compared to non-diabetic peers. Objective: The objective of the study was to evaluate the therapeutic effect of Tribulus terrestris (TT) and Cumminum cyminium (CC) against sexual dysfunction in males with diabetes. Methods: In-vivo animal models were utilized to find out Tribulus terristeris and Cumminum cyminium. Libido study: Sexually active male Wistar rats were divided into 5 groups, i.e., control, fluoxetine treated, fluoxetine with Tribulus terristeris, fluoxetine with Cumminum cyminium and fluoxetine with bupriprion. These rats were treated for 28 days by giving different drugs to different groups. Erection study: Male Wistar rats were divided into 5 groups (six in each group) i.e. control, diabetic rats, diabetic rats treated with Tribulus terristeris, diabetic rats treated with Cumminum cyminium and diabetic treated with insulin. The rat penile tissue was taken by scarifying the rats, and in-vitro contraction and relaxation were carried out in a two-chamber student organ bath. Sperm analysis: Sperm were collected from previously scarified rats in an erection study, and collected sperm were washed and counted (using Neubauer haemocytometer), and sperm motility was also studied. Results: Cumminum cyminium showed the significant reversal of loss of desire caused by fluoxetine which was comparable to standard drug bupropion. Insulin and Tribulus terristeris treated diabetic group of rats showed the lowest capability to relax, indicating setting up of erectile dysfunction. Diabetic rats exhibited a significant reduction in sperm density, % sperm motility, and % sperm viability. Insulin and C. cyminium treated diabetic rats showed significant improvement in sperm density, % sperm motility and % sperm viability. Conclusion: Tribulus terristeris at the dose of 100 mg/kg b.w was found to improve erectile function, whereas Cumminum cyminium at the dose of 150 mg/kg b.w was found to improve libido and sperm profile of fluoxetine treated rats.
Keywords: diabetic rats